The Differences of Marital Satisfaction of ODHA Couples with and without Depression Symptoms - Salahudin, Muhammad Ismail; Fitrikasari, Alifiati; Sofro, Muchlis Achsan Udji; Julianti, Hari Peni (UI Scholars Hub, 2018)
Introduction. HIV/AIDS disease has caused physical, social, and emotional problems to infected individuals and their spouses. ODHA couples have a prevalence of depression symptoms with physical complaints, which amounted to 12.7%. There is a relationship between love, communication, and physical intimacy to satisfaction in marriage. Depression in ODHA couples is correlated with marital satisfaction. This study aimed to analyze the differences of marital satisfaction of ODHA HIV negative couples who experience depression symptoms with ODHA who do not experience depression symptoms Methods. The research design was cross-sectional. The samples were 52 official couples of ODHA aged 18-60 years who had outpatient treatment in Poly of Infection Tropical RSUP. Dr. Kariadi Semarang and met the criteria of research inclusion. Sampling technique was conducted with consecutive sampling method. Depression status was measured by the beck depression inventory (BDI) instrument and marital satisfaction was measured by ENRICH marital satisfaction scale (EMS). Processing and data analysis using SPSS program. The relationship analysis test using chi-square test. Results. Subjects who did not experience depression 78.8% and those with depression 21.2% consisted of mild 9.6%, moderate 11.6%, and severe 0%. No subjects were found to be unsatisfied with their marriage, 55.8% were very satisfied and 44.2% were satisfied. There was no significant difference between marital satisfaction of ODHA HIV negative couples with depression symptoms and without depression symptoms (p = 0,595). There was a significant difference between the marital satisfaction of ODHA HIV negative couples with depression symptoms and without depression symptoms in communication (p = 0.021), conflict resolution (p = 0.025), use of leisure activities (p = 0.025), and sexual activities (p = 0.007) Conclusion. There was no difference between the marital satisfaction of ODHA HIV negative couples with depression symptoms and without depression symptoms. There was a significant difference between the marital satisfaction of ODHA HIV negative couples with depression symptoms and without depression symptoms in communication, conflict resolution, the use of leisure activities, and sex activities.